THE ANALYSIS OF ROBERT COX'S CRITICAL THEORY: THE INHERENT SUBJECTIVITY AND PURPOSEFUL NATURE OF THEORETICAL FRAMEWORKS - Jundana, Aizza (SIYAR Journal, 2024)
Robert Cox's assertion that “theory is always for someone and for and some purpose" is a fundamental tenet of political science and international relations, emphasizing the inherent subjective and purposeful nature of theoretical frameworks. This study critically examines Cox's contribution to International Relations (IR) through critical theory. This study is based on a qualitative research approach and uses an extensive literature review to gather relevant information, thorough analysis of existing journals and books, providing a comprehensive understanding of Cox's critical theory and its impact on the field of IR. The finding of this study highlights the need for continued evaluation of Cox popular IR theory and the application of Cox's theoretical foundations to deepen understanding of the world. Cox's critical theory brings new perspectives and contributes significantly to the diversity of theoretical frameworks in IR. This study highlights the transformative impact of Cox's critical approach and its relevance to shaping contemporary debates in the international relations.